Incidence and predictors of severe anemia in Asian HIV-infected children using first-line antiretroviral therapy - Torsak Bunupuradah (2018)
Background: There are limited data on treatment-related anemia in Asian HIV-infected children. Methods: Data from Asian HIV-infected children aged < 18 years on first-line highly active antiretroviral therapy (HAART) were used. Children who had pre-existing severe anemia at baseline were excluded. Anemia was graded using the United States Division of AIDS (DAIDS) 2004 table. Potential risk factors for severe anemia were assessed by logistic regression. Results: Data from 1648 children (51.9% female, 62.8% World Health Organization (WHO) stage 3/4) were analyzed. Median (interquartile range) age was 6.8 (3.7-9.6) years, CD4% was 9 (3-16)%, and plasma HIV-RNA was 5.2 (4.7-5.6) log 10 copies/ml at HAART initiation in those with available testing. The most common regimens were stavudine/lamivudine/nevirapine (42%) and zidovudine/lamivudine/nevirapine (25%). Severe anemia was identified in 47 (2.9%) children after a median time of 6 months after HAART initiation, with an incidence rate of 5.4 per 100 child-years. Mild anemia or moderate anemia at baseline (p = 0.024 and p = 0.005, respectively), previous or current use of zidovudine (p < 0.0001 and p = 0.013, respectively), and male sex (p = 0.008) were associated with severe anemia. Higher weight-for-age z-score (p = 0.004) was protective. Conclusions: The incidence of severe anemia in Asian HIV-infected children after HAART initiation was low and mainly occurred during the first few months after HAART initiation. Mild to moderate anemia at baseline and using zidovudine were independent risk factors for the development of severe anemia. © 2013 International Society for Infectious Diseases.